Methanol: The Basic Chemical and Energy Feedstock of the Future Asinger's Vision Today - Bertau, Martin.; Bertau, Martin.; Offermanns, Heribert.; Offermanns, Heribert.; Plass, Ludolf.; Plass, Ludolf.; Schmidt, Friedrich.; Schmidt, Friedrich.; Wernicke, Hans-Jürgen.; Wernicke, Hans-Jürgen. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This compendium offers a visionary yet unbiased view of modern methanol technology. Based on the groundbreaking 1986 publication Methanol by Friedrich Asinger, this book includes contributions by more than 40 experts from industry and academia. The authors and editors provide a comprehensive exposition of methanol chemistry and technology which is useful for a wide variety of scientists working in chemistry and energy related industries. In addition, this book is of interest to academic researchers, decision-makers and organisations concerned with the future of chemical and energy feedstocks.